Management of Sendang Maibit Tourism Based on Community-Based Tourism in Mibit Village, Rengel District, Tuban Regency - Fatimah, Fifi Fitria Nurul; Taufiq, Ahmad; Musta'ana, Musta'ana (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study aims to examine the implementation of Community Based Tourism (CBT) in the management of Sendang Maibit tourism in Maibit Village, Rengel District, Tuban Regency. Using a qualitative approach, this study involves field observations, in-depth interviews, and document studies to understand the role of local communities in tourism management. The results of the study show that the community actively participates in tourism planning and management, especially through tourism awareness groups (pokdarwis). Although the CBT approach has had a positive impact, several challenges remain, including limited management capacity, inadequate infrastructure, and lack of tourism promotion. However, with the right support from the government and the private sector, Sendang Mibit has great potential to develop as a sustainable community-based tourism destination. This study highlights the importance of community empowerment and collaboration between stakeholders in achieving the success of community-based tourism.